The effect of interacting dark energy on local measurements of the Hubble constant - Odderskov, Io; Baldi, Marco; Amendola, Luca (Journal of cosmology and astroparticle physics, 2016)
In the current state of cosmology, where cosmological parameters are being measured to percent accuracy, it is essential to understand all sources of error to high precision. In this paper we present the results of a study of the local variations in the Hubble constant measured at the distance scale of the Coma Cluster, and test the validity of correcting for the peculiar velocities predicted by gravitational instability theory. The study is based on N-body simulations, and includes models featuring a coupling between dark energy and dark matter, as well as two ΛCDM simulations with different values of σ 8 . It is found that the variance in the local flows is significantly larger in the coupled models, which increases the uncertainty in the local measurements of the Hubble constant in these scenarios. By comparing the results from the different simulations, it is found that most of the effect is caused by the higher value of σ 8 in the coupled cosmologies, though this cannot account for all of the additional variance. Given the discrepancy between different estimates of the Hubble constant in the universe today, cosmological models causing a greater cosmic variance is something that we should be aware of.